THE IMPORTANCE OF INFORMATION RESOURCES IN FOREIGN LANGUAGE TEACHING VIA THE INTERNET - Mansurova, Shohista (Журнал иностранных языков и лингвистики, 2023)
In our article, the most important feature of multimedia is the integration of various information and the effectiveness of training, which affects many human emotions and evokes an emotional reaction in the student. The nature of interactivity, the ability to control the process of information presentation attracts the student to an active learning process, stimulates his cognitive activity and helps to maintain a stable motivation to study.